Identification of HOTS Problem Solving Ability of High School Students Using Two Tier Diagnostic - Frenanto, Allan; fatqurhohman, fatqurhohman; Rhomdani, Rohmad Wahid (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
The purpose of this study is to describe HOTS problem solving skills for high school students through the use of the 2nd Tier Diagnostic. The research is conducted using the descriptive qualitative method. SMAN Balung MIPA 4 Research subjects at Jember Regency Data Collection Techniques in the form of Written Test Questions and Semi-Structured Interviews Data on Problem Solving Skills using 5 Stages Krulick & Rudnick Stages Read and Think, Explore and plan, select a strategy, Find and Answer, Reflect and Extend. The Two Tier Diagnosis Method is composed of two stages. First, students write down how they get the answers, and second, they write down the reasons why they choose that method. The study showed that students with high mathematical problems solving skills were able to write mathematical symbols well, even write answers consistently, and write the final solution along with the question. Students with moderate abilities were unable to write the mathematical symbols well, and even wrote the stages of completion incorrectly, resulting in the majority of the final answers being wrong.